Aspects of Digital Multilingualism in Twenty-First Century Retail Banking in Nigeria. - Akande, Akinmade; Robbin, Anjola; Okesola, Saheed (Language Matters: Studies in the Languages of Africa, 2025)
This article investigated the use of multiple languages on ATMs in selected banks located in Oyo and Osun states, Nigeria. The study examined the number of languages used on the ATMs in these banks and the prospects and challenges of using multiple languages on ATMs by drawing data from surveys and interviews with bankers. The study found the dominant use of English, minimal use of Nigerian Indigenous languages, and one instance of Nigerian Pidgin. They concluded that there is a growing interest in Nigerian Pidgin in banking.